2014
DOI: 10.1111/jre.12220
|View full text |Cite
|
Sign up to set email alerts
|

Periodontopathogens and human β‐defensin‐2 expression in gingival crevicular fluid from patients with periodontal disease in Guangxi, China

Abstract: The prevalence, composition and CN of periodontopathogens were closely related to the severity of periodontal disease, and the red complex was related to the severity of clinical symptoms of periodontal diseases. The concentration of hBD-2 in gingival crevicular fluid from periodontal disease sites was higher than that in gingival crevicular fluid from healthy sites, which suggests that hBD-2 expression might be up-regulated by periodontopathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
(62 reference statements)
1
11
0
15
Order By: Relevance
“…Albeit nonstatistically significant, hBD-1 and hBD-2 levels were slightly lower in patients with a PSR/CPITN index of 3 and 4 when compared to those with a PSR/CPITN index of 1 and 2. We believe this small reduction in hBD-1 and hBD-2 levels in the saliva occurred due to the degradation of hBD by proteases released at sites that are more commonly affected by periodontopathogens, as hypothesized by Yong et al 27 who verified higher hBD-2 levels in the saliva of patients with gingivitis than among those with periodontitis. Another possible explanation to this reduction could be the lower average number of teeth in Group 3.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Albeit nonstatistically significant, hBD-1 and hBD-2 levels were slightly lower in patients with a PSR/CPITN index of 3 and 4 when compared to those with a PSR/CPITN index of 1 and 2. We believe this small reduction in hBD-1 and hBD-2 levels in the saliva occurred due to the degradation of hBD by proteases released at sites that are more commonly affected by periodontopathogens, as hypothesized by Yong et al 27 who verified higher hBD-2 levels in the saliva of patients with gingivitis than among those with periodontitis. Another possible explanation to this reduction could be the lower average number of teeth in Group 3.…”
Section: Discussionmentioning
confidence: 63%
“…The quantification of hBD-1 and hBD-2 by ELISA has been widely used for the determination of salivary levels of these peptides. 14,26 There are conflicting reports in the current literature regarding hBD-1 and hBD-2 expression in periodontal disease, as some studies suggest upregulated hBD expression 8,14,27,28 whereas some suggest a down regulated expression of this peptide. 29,30 In addition, previous studies found high concentrations of these peptides only after stimulation with periodonto pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been shown by Kumar et al (42). The fact that all types of bacteria studied could be detected, even in healthy controls, might indicate that the presence of periodontal pathogens does not necessarily lead to periodontal diseases (1). However, these species show just a small percentage of whole bacteria, and the open-ended approach of their study may not be geared to indicate an association of this species with the disease (20).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a strong association between the presence of P. gingivalis and periodontitis, but did not find any association between the presence of P. gingivalis and gingivitis (1,12,44,45). Although a number of putative bacteria are considered to be associated with chronic periodontitis, it has become clear that other factors are involved in the etiology of several types of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation